Evaluation of the Implementation of the Field Work Practice Program - Muh. Nasrullah; Nur Anisa; Sitti Hardiyanti Arhas (Asha Publishing, 2024)
School is the first and main step in developing the talents and skills possessed by everyone. This study aims to determine the management and implementation of the field work practice program at SMKN 1 Selayar with the type of qualitative research and data collection techniques through interviews and documentation. Based on the results of this study, it is shown that the evaluation of the management and implementation of the field work practice program at SMKN 1 Selayar can be seen from the indicators of preparation, demonstration, imitation, practice, and evaluation in the